OCITOCINA SINTÉTICA NO TRABALHO DE PARTO INDUZIDO E SUAS REPERCUSSÕES MATERNO-FETAIS - Santos, Kleviton Leandro Alves dos; Farias, Cinthia Rafaela Barbosa Lima; Cavalcante, Jaylla Silva; Duarte, Ana Paula Ramos da Silva; Santos, Ewerton Amorim dos (Gep News, 2019)
Trabalho apresentado durante o I MASMI